A Green Approach to the Production of Hybrid Diindolylmethane-Phenylboronic Acids via a 3MCR: Promising Antineoplasic Molecules. (5th August 2013) - Zarco Juarez, Mónica; Martínez, Joel Omar; Noguez Cordova, Olivia; Nicolás Vazquez, María Inés; Ramírez-Apan, Teresa; Pérez Flores, Javier; Miranda Ruvalcaba, René; Arroyo Razo, Gabriel Arturo
Abstract : The current role of the "Green Chemistry Protocol" in multicomponent reactions is first highlighted. Then, the green approach to the production of three novel hybrid diindolylmethanes-phenylboronic acids via a 3MCR is discussed, which features the following: solventless conditions, the use of microwave irradiation to activate the reactions, the absence of catalyst, and an efficient atom economy. The products were achieved with moderate yields (41–61%) within a short time frame (5 min) and appropriately characterized by elemental analysis and spectroscopic methods (NMR: 1 H, 13 C, 11 B; MS: EI, CI, FAB +, HRMS). During the FAB + MS determinations, various artifacts that are associated with the boron atom via an interaction with thioglycerol from the matrix were noted in the corresponding FAB + mass spectra; in addition, the accurate mass determination of these adducts unequivocally confirmed the presence of the target molecules. Moreover, the activity of these target molecules was evaluated in the presence of six cancer cell lines (U251 = glia of the central nerve system, PC-3 = prostate, K562 = leukemia, HCT-15 = colon, MCF-7 = breast, and SKLU-1 = lung), which resulted in the meta -regioisomer being the most active. Finally, the products were also analyzed using computational chemistry in order to determine their most stable geometries and reactivities by computing the respective molecular electrostatic potentials.